2016
DOI: 10.1111/bij.12852
|View full text |Cite
|
Sign up to set email alerts
|

Repeated evolution of local adaptation in swimming performance: population-level trade-offs between burst and endurance swimming inBrachyrhaphisfreshwater fish

Abstract: Specialization is fundamentally important in biology because specialized traits allow species to expand into new environments, in turn promoting population differentiation and speciation. Specialization often results in trade‐offs between traits that maximize fitness in one environment but not others. Despite the ubiquity of trade‐offs, we know relatively little about how consistently trade‐offs evolve between populations when multiple sets of populations experience similarly divergent selective regimes. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 78 publications
0
10
2
Order By: Relevance
“…Notably, our analyses indicated that neither standard length nor body shape were the strongest predictors of swimming speed performance, contrary to reported observations and theoretical predictions of morphological differentiation (Langerhans, 2008;Vogel, 1994;Webb, 1984). Indeed, body size and shape divergence may emerge in response to a range selective pressures imposed upon fish in different flow environments (Herler et al, 2010;Ingley et al, 2014;Ingley et al, 2016;Johnson et al, 2014).…”
Section: Relationship Between Swimming Performance Body Morphologycontrasting
confidence: 99%
“…Notably, our analyses indicated that neither standard length nor body shape were the strongest predictors of swimming speed performance, contrary to reported observations and theoretical predictions of morphological differentiation (Langerhans, 2008;Vogel, 1994;Webb, 1984). Indeed, body size and shape divergence may emerge in response to a range selective pressures imposed upon fish in different flow environments (Herler et al, 2010;Ingley et al, 2014;Ingley et al, 2016;Johnson et al, 2014).…”
Section: Relationship Between Swimming Performance Body Morphologycontrasting
confidence: 99%
“…These population differences in burst and steady swimming were evident in a functional trade‐off, where individuals with high fast‐start performance exhibited lower critical swimming speeds and vice versa . Functional trade‐offs between burst and steady swimming have been documented in poeciliids (Ingley et al, ; Langerhans, ) and other fishes (Ellerby & Gerry, ; Yan, He, Cao, & Fu, ) and underlie population differences in morphology when divergent selection favours different aspects of locomotion performance (Langerhans, Layman, Langerhans, & Dewitt, ). Fundamental constraints in combination with replicated environmental gradients may therefore be important contributors to convergent morphological evolution, both across independent lineages that have colonized H 2 S‐rich environments (Tobler et al, ) and in other systems (Ingley et al, ; Langerhans, ).…”
Section: Discussionmentioning
confidence: 99%
“…Methods for the quantification of fast-start responses were adapted from previous studies (Ingley, Camarillo, Willis, & Johnson, 2016;Langerhans et al, 2004). For each trial, we placed a fish into a clear acclimation cylinder (5.5 cm in diameter) within a larger test arena (circular tank with a 40 cm diameter).…”
Section: Burst Swimming Performancementioning
confidence: 99%
“…Locomotor performance is positively related to survival (Husak, ; Teplitsky et al, ), and can improve prey hunting (Budick & O'Malley, ; Higham, ), optimize refuge use (Martín & López, ) and facilitate escape from predators (Arendt, ; McGee et al, ; Oufiero, Walsh, Reznick, & Garland, ). In fact, predator pressure selects for improved locomotor performance (Ingley, Camarillo, Willis, & Johnson, ): locomotor performance is increased in open areas, probably as a consequence of more intense predator pressure (Vanhooydonck & Van Damme, ).…”
Section: Introductionmentioning
confidence: 99%